2022
DOI: 10.1007/s00281-022-00933-9
|View full text |Cite|
|
Sign up to set email alerts
|

Narcolepsy: a model interaction between immune system, nervous system, and sleep-wake regulation

Abstract: Narcolepsy is a rare chronic neurological disorder characterized by an irresistible excessive daytime sleepiness and cataplexy. The disease is considered to be the result of the selective disruption of neuronal cells in the lateral hypothalamus expressing the neuropeptide hypocretin, which controls the sleep-wake cycle. Diagnosis and management of narcolepsy represent still a substantial medical challenge due to the large heterogeneity in the clinical manifestation of the disease as well as to the lack of unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 115 publications
(125 reference statements)
0
8
0
1
Order By: Relevance
“…According to some studies, narcolepsy affects more males than females and children, while some say the contrary. It can affect any age group regardless of gender [ 21 ]. The typical tetrad of narcolepsy was given in the year 1956 by Yoss and Daly, which included EDS, hypnagogic hallucinations, sleep paralysis, and cataplexy [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to some studies, narcolepsy affects more males than females and children, while some say the contrary. It can affect any age group regardless of gender [ 21 ]. The typical tetrad of narcolepsy was given in the year 1956 by Yoss and Daly, which included EDS, hypnagogic hallucinations, sleep paralysis, and cataplexy [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Latorre et al review the strong HLA gene polymorphisms found in GWAS studies of narcolepsy and the emerging data on autoreactive T cells against the hypothalamic hypocretin/orexin-producing neurons that regulate sleep. 4 It has recently been recognized that inflammation plays a role in outcome after cerebrovascular diseases like ischemic stroke. DeLong et al in this issue examine the initiation and resolution of the inflammatory responses after stroke with the complex impacts of leukocytes and microglia on outcomes.…”
Section: Neuroimmune Interactions In Health and Diseasementioning
confidence: 99%
“…A close connection between the immune system and sleep-regulating mechanisms has been suggested, such as the link between narcolepsy and particular human leukocyte antigen (HLA) antigens [ 26 ]. Therefore, a similar association between KLS and HLA has been proposed.…”
Section: Etiology: Proposed Mechanismsmentioning
confidence: 99%